769 Differential pharmacological modulation of arrhythmic phenotype in catecholaminergic polymorphic ventricular tachycardia: not all betablockers are the same. (8th December 2021) - Kukavica, Deni; Mazzanti, Andrea; Trancuccio, Alessandro; Giannini, Gala; Marino, Maira; Mohsin, Muhammad; Bloise, Raffaella; Napolitano, Carlo; Priori, Silvia G
Abstract: Aims: Catecholaminergic polymorphic ventricular tachycardia (CPVT) is an inherited arrhythmogenic disorder that predisposes patients to develop catecholamine-mediated ventricular arrhythmias (VA), manifesting as exercise- or emotion-induced syncope or cardiac arrest. Due to the catecholaminergic nature of CPVT, exercise stress test (EST) represents the most important diagnostic test. Although widely used in clinical practice to monitor response to therapy, how BBs modulate the occurrence of ventricular arrhythmias during EST in CPVT patients is unclear. To compare the relative efficacy of different classes of betablockers (BBs, β1-selective BBs vs. nadolol) on the arrhythmic manifestations during ESTs performed off-therapy and on-therapy in patients with CPVT. Methods and results: We selected 72 patients (45 females) with pathogenic or likely pathogenic variants on RYR2 or CASQ2 from our cohort of 246 genotype-positive CPVT patients, who had at least one EST off-therapy and at least one EST during BB therapy. Overall, 507 ESTs (77 ESTs off-therapy, 29 ESTs during β1-selective BBs, and 401 during nadolol) were prospectively collected over 11.1 ± 6.8 years of follow-up and analysed, with a median of 5 ESTs per patient [interquartile range (IQR): 3–10 ESTs, range: 2–27 ESTs]. In the absence of therapy, VT was documented in 46/77 (60%) cases. BB therapy with nadolol significantly reduced VT at EST to 10% (41/398; P  < 0.001). Conversely, β1-selective BBs did not significantly decrease VT incidence at EST (13/29, 45%, P  = 0.289) as compared to baseline. Importantly, nadolol was superior in preventing VT both when compared to off-therapy [odds ratio (OR): 33.9, 95% confidence interval (CI): 15.6–73.5, P  < 0.001] but also when compared to β1-selective BBs [OR: 18.0, 95% CI: 6.0–53.5, P  < 0.001]. Although β1-selective BBs significantly increased the total exercise time free of arrhythmias (median 248 s, IQR: 212–315 s) as compared to baseline (median 83 s, IQR: 12–207 s; P  < 0.001), arrhythmia-free exercise time during nadolol (median 381 s, IQR: 251–543 s) was significantly longer as compared to both off-therapy ( P  < 0.001) and β1-selective BBs ( P  = 0.020). Multivariate mixed effects logistic regression confirmed that at parity of time of occurrence of first arrhythmia and percentage of maximal heart rate reached, both of which were significantly associated to VT occurrence ( P  = 0.001 for both), the use of nadolol (OR: 0.23; 95% CI: 0.09–0.60; P  = 0.011) was independently associated with decreased incidence of VT. Focusing on the 14 patients (overall 133 ESTs) who had at least one ESTs after the occurrence of VT in nadolol, we dissected the effect of dose increase on the probability of VT reoccurrence. Following the documentation of breakthrough VT, increasing the dose of nadolol by 0.5 mg/kg reduced by 2.5 times the probability of having a recurrence of VT (OR: −2.49, 95% CI: −3.96 to − 1.0; P  < 0.001). Conclusions: Once CPVT is diagnosed, nadolol at 1 mg/kg/day should be used as preferred therapy as it has been shown to suppress VT in most patients. In rare instances in which VA persist despite an adequate nadolol dose, dose increase to 1.5 mg/kg/day may represent an efficacious antiarrhythmic strategy.